Perovskitas baseadas no PZT e PLZT sintetizadas usando o método dos complexos oxidantes de peróxido (OPM) - Gonçalves, Mayra Dancini (2011)
Were synthesized by the OPM, the solid solutions of Pb(Zr1-xTix)O3 with x = 0.8, 0.48 and 0.2, and also the lanthanum modified lead zirconate titanate compositions (Pb0.95La0.05) (Zr1-xTix)O3 with x = 0.8 and 0.2. This paper reports the first synthesis of PLZT by means of the OPM route. The techniques for X-ray diffraction and Raman spectroscopy at room temperature showed that the PZT and PLZT compositions Ti-rich have essentially tetragonal structure and the compositions Zr-rich are rhombohedral. Since the composition with x = 0.48 known as the morphotropic phase boundary (MPB) shows a mixture of both structures. Analysis by BET isotherms showed that the powders have high surface area even when thermally treated at 700 ° C, confirming its higher reactivity compared to powders obtained by other synthetic methods. At this temperature, images from scanning electron microscopy reveal the formation of aggregates of nanometric spherical particles already in the process of sintering due to diffusion of matter and formation of necks between them. Since these materials have great technological importance, the powders were conformed to the shape of discs and sintered in two types of ovens, conventional and microwave ones, for evaluation and comparison of morphological, structural and dielectric properties. The composition of PZT in the MPB showed dielectric constant higher than the values reported in the literature, both for the samples sintered in a conventional oven (12330) as for the sintered using microwave energy (17900). However, the Curie temperature also showed anomalous values of 460 and 465 ° C, respectively. It can be attributed to the influence of the absence or lower content of oxygen vacancies in the powders synthesized by means of the OPM route.